Sustainable edible coatings on physicochemical properties and storability of strawberry fruits - Swarna, T; Radhajogita, M; Bhawana; Nishikant, Y; Megha, T (Plant Science Today, 2026)
Despite of popularity for vibrant flavour and colour, strawberries rapidly lose commercial potential due to their delicate nature and high perishability, which poses a major hurdle for growers and retailers alike. Nowadays, fruit researchers are concerned about edible fruit coatings as a solution to this problem. In this present experiment, Aloe vera (L.) Burm.f. (AV) 60 %, sodium alginate (SA) 2 %, chitosan (C) 2 %, methyl cellulose (MC) 2 %, AV 60 % + C 2 %, AV 80 % + C 2 %, AV 60 % + ascorbic acid (AA) 2 %, C 2 % + AA 2 % edible coatings were applied on strawberry fruits alike other research. The treated and untreated fruits were maintained under room temperature and relative humidity (60 ± 5 oC). After fruit coating, observations were conducted at 0, 2 and 4 days. In comparison to all fruit coatings, SA 2 % was found to be most effective in preserving vitamin C, total sugar, reducing sugar, non-reducing sugar, titrable acidity, total antioxidant content, total anthocyanin content, total phenol content, total flavonoid content, as well as physiological weight loss (49.13), firmness, length, breadth and additionally increased pH. In conclusion, compared to other coated fruits and T9 (uncoated fruits), the SA 2 % (T4) coating was a most successful method for preserving the post-harvest quality of strawberry fruits under ambient conditions.